Prevalence of Helicobacter pylori Infection, Its Virulent Genotypes, and Epstein-Barr Virus in Peruvian Patients With Chronic Gastritis and Gastric Cancer - Castaneda, Carlos (2019)
Purpose: Helicobacter pylori (HP) and Epstein Barr virus (EBV) infections induce chronic gastritis (CG) and are accepted carcinogenics of gastric cancer (GC). Our objective for this study was to determine the prevalence of these agents and clinicopathological features of GC and CG associated with the infection. Patients and methods: A single-center cohort of 375 Peruvian patients with GC and 165 control subjects with CG were analyzed. Evaluation of HP and EBV genes was performed through quantitative polymerase chain reaction. Results: Prevalence of HP was 62.9% in the whole population and 60.8% in the GC subset. The cagA gene was detected in 79.9%; vacAs1 and vacAm1 alleles in 41.6% and 60.7%, respectively; and concurrent expression of vacAs1 and vacAm1 in 30.4% of infected patients in the whole series. The prevalence of EBV was 14.1% in the whole population and was higher in GC (P < .001). Coinfection of HP and EBV was found in 7.8% and was also higher in GC in univariate (P < .001) and multivariate (P = .011) analyses. Infection rates of HP and EBV were not associated with a geographic location in the whole series. Few clinicopathological features have been associated with infectious status. Conclusion: Prevalence of HP infection and virulent strains are high in the Peruvian population. Infection by EBV was more frequent in patients with GC.